A procedure for the design of storage facilities for instream erosion control in urban streams. - MacRae, Craig R. (University of Ottawa (Canada), 1991)
It is demonstrated that the greatest increase in erosion potential is associated with moderate flow events (recurrence interval less then 1:1.5 years). The importance of the bank toe stratigraphic unit is also explored using field observations of bank structure. The implication on design methodology is the need to address scour potential on a point by point basis about a channel perimeter to account for variations in material characteristics and bank structure relative to the change in flow geometry. Channel response scenarios showing initial, intermediate and long term channel form in response to an alteration in flow and sediment regimes are developed; wherein channel form is initially determined by the relative difference between the erodibility of the bed and least resistance bank toe stratigraphic units, and ultimately by the relative difference between sediment load characteristics and stream competence. Consequently, the degree of storage control must balance erosive and sedimentation processes to ensure long term stability. These two process are incorporated into a proposed index of scour potential. The index compares sediment mass balance at a point on the channel periphery before and after development. Scour potential is addressed by creating a sub-index which is equated with excess shear potential. Integration of the sub-index with respect to time provides an index which is a measure of the temporal variation in erosion potential. It is argued that changes in erosion potential are minimized if the index is maintained constant with pre-development values. It follows that the channel should remain stable if the transverse distribution of the index is also maintained constant with the pre-development distribution. The ability of the index to represent scour potential is demonstrated through a one to one correspondence between the rank of index values with a ranking of depths of degradation as predicted using a one-dimensional mobile bed model. Several bed load sediment transport relations based on excess shear stress concepts are evaluated as a basis for the estimation of mass balance. It is acknowledged that the relation used will vary with site specific conditions and user preference. A procedure is then proposed for the development of flow criteria which would limit changes in flow geometry associated with urbanization by accounting for variations in boundary material resistance to scour about the channel perimeter. The amount of storage control required was found to vary with the resistance to scour of the least resistant bed or bank stratigraphic unit. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.